Prevalence and distribution of intestinal parasites in stray dogs in the northwest area of Mexico - Trasviña-Muñoz, Enrique; López-Valencia, Gilberto; Álvarez Centeno, Pedro; Cueto-González, Sergio A; Monge-Navarro, Francisco J; Tinoco-Gracia, Luis; Núñez-Castro, Karla; Pérez-Ortiz, Paulina; Medina-Basulto, Gerardo E; Tamayo-Sosa, Alma R; Gómez-Gómez, Daniel (Austral Journal of Veterinary Sciences, 2017)
ABSTRACT. Zoonotic parasitic infections are a major global public and veterinary health problem and widespread among stray dogs. The objective of this study was to establish the prevalence of intestinal parasites in stray dogs in the urban, rural and coastal areas of Mexicali County in northwest Mexico. In 2014, from January to December, 380 stray dogs were captured. The entire small intestine, cecum and faeces samples were collected and examined by using simple zinc sulfate flotation and Lugol’s solution staining. Data were statistically analysed. Overall, about 21.5% of examined dogs were found positive for intestinal parasites. Toxocara canis was the most frequent detected parasite, with a prevalence of 7.1%, followed by Toxascaris leonina (5.5%), Cystoisospora spp. (5.0%), Taenia spp. (3.9%) and Dipylidium caninum (2.8%). Dogs were more frequently found to be infected with a single genus of intestinal parasite (18.7%) than co-infected (2.8%). Intestinal parasites were more prevalent in samples from the coastal area (25%) than in those from the rural (24.4%) and urban (20.6%) areas, however, only statistical association was found between capture area and specific intestinal parasitic infection. There were significant differences in the prevalence of taeniasis among two age groups (P<0.01). A seasonal peak of prevalence for intestinal parasitic infections was found during spring (P<0.05), corresponding with a seasonal peak of prevalence of T. canis (P<0.05). The wide range of isolated parasites indicated that people residing in this area are at risk of exposure to these potentially hazardous zoonotic pathogens.